2021
DOI: 10.1037/aap0000249
|View full text |Cite
|
Sign up to set email alerts
|

Stress, mental health, and self-care among refugee teachers in Malaysia.

Abstract: The mental health of post-conflict refugee teachers is understudied, yet critically important given the current refugee crisis which has displaced more than 70 million people (UNHCR, 2019). Teachers in hidden refugee schools 1 are often refugees themselves, have little teacher education, and are faced with overwhelming classroom demands and other unique stressors. This study utilizes a mixed method design to examine stress, mental health (i.e., depression, and anxiety), and self-care among teachers in hidden r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…In refugee settings, children may be at increased risk of violence due to overcrowding and resource constraints, a general lack of security, political tensions, and weak child protection referral and response systems [ 31 , 32 ]. In these contexts, school violence may be further exacerbated by teachers’ high levels of stress and histories of trauma, which may affect their use of violent discipline and ability to effectively supervise students in class [ 33 , 34 ]. Norms that promote or condone use of violence may also contribute to high levels of teacher and peer violence [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In refugee settings, children may be at increased risk of violence due to overcrowding and resource constraints, a general lack of security, political tensions, and weak child protection referral and response systems [ 31 , 32 ]. In these contexts, school violence may be further exacerbated by teachers’ high levels of stress and histories of trauma, which may affect their use of violent discipline and ability to effectively supervise students in class [ 33 , 34 ]. Norms that promote or condone use of violence may also contribute to high levels of teacher and peer violence [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cowling and Anderson (2021) examine teacher perceptions of Chin refugee students and find evidence that these students often struggle with their education due to language difficulties, lack of resources, experienced discrimination, fear caused by their lack of legal status, and cultural values within their community that devalue education. In a mixed methods study, Gosnell et al (2021) find that teachers of refugees in Malaysia (predominantly refugees themselves) struggle with mental health problems, stress, and low levels of self-care, with younger teachers and female teachers struggling in particular. In addition, consistent with Cowling and Anderson (2021) and Gosnell et al (2021) found that these teachers also struggled with fear due to their precarious legal status, discrimination, and lack of resources.…”
mentioning
confidence: 99%
“…In a mixed methods study, Gosnell et al (2021) find that teachers of refugees in Malaysia (predominantly refugees themselves) struggle with mental health problems, stress, and low levels of self-care, with younger teachers and female teachers struggling in particular. In addition, consistent with Cowling and Anderson (2021) and Gosnell et al (2021) found that these teachers also struggled with fear due to their precarious legal status, discrimination, and lack of resources.…”
mentioning
confidence: 99%
See 2 more Smart Citations